North Korea: Country Without Freedom - Putri Tri Aurasifa; Khairilla Ayurie; Riyanda Suciati; Yusawinur Barella (PT Syamilah Literasi Islami, 2024)
The Democratic People's Republic of Korea, also known as North Korea, is a country in East Asia, with Pyongyang as its capital. Since the founding of North Korea with Kim Il Sung as the first leader, he created Juche as a state ideology derived from the absorption of Marxism and communism ideologies According to John Locke, human rights are inherent privileges bestowed upon people by God. This paper aims to describe the basic rights that have been taken away in North Korea. This research uses a qualitative method, which is a method based on observation of accurate data collection from various trusted sources. Data collection is carried out through stages such as 1) reading and understanding the contents of journals and articles obtained from the internet. 2) sorting the data. 3) detailing the data. 4) data analysis the notoriously closed communist nation of North Korea establishes its control and strength on its own Conflicts and issues abound in this nation, including limitations on women's rights and the appropriation of both native and foreign labor. The North Korean government, in fact, has taken no real concrete action, there are still more human rights abuses happening. Human rights breaches persist despite the imposition of numerous sanctions by the international community and the UN Security Council. It is time for groups working with North Korea and the international community to organize and schedule more initiatives aimed at advancing human rights, if not bettering them.